A Systematic Literature Review of Technology-Based Learning Models to Improve Numeracy Literacy in the Indonesian Context - Nur, Fitriani; Mania, Sitti; Amin, Badaruddin; Wahid, Fatin Nabilah Abdul (FKIP Universitas Lampung, 2025)
A Systematic Literature Review of Technology-Based Learning Models to Improve Numeracy Literacy in the Indonesian Context. Objectives: Technology-based learning is a learning approach that fosters student interaction with various learning resources. This study aims to analyze the characteristics of technology-based learning models that can improve numeracy literacy. Methods: This research employed a Systematic Literature Review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Data were collected using the Publish or Perish tool from Scopus and Google Scholar databases, limited to articles published between 2016 and 2025. A total of 25 articles were deemed eligible for analysis. Findings: The results of this study indicate that various technology-based learning models facilitate the improvement of students' numeracy literacy skills. These models integrate technology to create learning that supports a more concrete understanding of numeracy concepts. In addition, this study also identifies the types of technologies used in technology-based learning models, which consist of four main categories: hardware, general software, mathematical software, and online resources. Notably, the most prominent findings highlight the use of General Software and Online Resources, which are widely applied in various learning models to support students’ numeracy literacy development. Conclusion: This study concludes that technology-based learning models have the potential to significantly enhance students’ numeracy literacy by implementing various forms of technology into the learning process. These models not only provide a more concrete understanding of numeracy concepts but also create interactive and engaging learning environments. The contribution of this research provides a solid basis for educators to adopt more effective and relevant technology-based learning models to improve students' numeracy literacy. Keywords: learning model, numeracy literacy, technology.